2018
DOI: 10.1021/acs.organomet.8b00069
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studies on the Dirhodium-Catalyzed [3 + 2] and [3 + 3] Cycloaddition Reactions of Enol Diazoacetates with Isoquinolinium Methylide: Mechanism, Selectivity, and Ligand Effect

Abstract: The reaction mechanisms of dirhodium-catalyzed [3 + 2] and [3 + 3] cycloaddition between enol diazoacetate and isoquinolinium methylide have been studied in detail using density functional theory and a solution-phase translational entropy model. The reaction starts with the formation of a metallic carbene intermediate first, from which two competing reaction channels of [3 + 2] and [3 + 3] cycloaddition take place. For CAT1-catalyzed reactions, the calculated activation free energy barriers for [3 + 3] and [3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 95 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Recent studies of this reaction using copper(I) catalysis 39 Products of [3+2]-cycloaddition were obtained in moderate yields via direct catalyst-free treatment of a D-A cyclopropene with a methylide. The experimental data was consistent with a recent theoretical study 50 that confirmed the [3+3]-cycloaddition as the major reaction pathway with Rh 2 (S-PTIL) 4 catalyst, and that preferential [3+2]-cycloaddition occurred in reactions catalyzed by electron-deficient Rh 2 (CF 3 COO) 4 and the chiral rhodium(II) catalyst Rh 2 (S-TCPTTL) 4 which has greater steric repulsions from its ligands compared to Rh 2 (S-PTIL) 4 . 50…”
Section: N-acyliminopyridinium/quinolinium Ylidessupporting
confidence: 92%
“…Recent studies of this reaction using copper(I) catalysis 39 Products of [3+2]-cycloaddition were obtained in moderate yields via direct catalyst-free treatment of a D-A cyclopropene with a methylide. The experimental data was consistent with a recent theoretical study 50 that confirmed the [3+3]-cycloaddition as the major reaction pathway with Rh 2 (S-PTIL) 4 catalyst, and that preferential [3+2]-cycloaddition occurred in reactions catalyzed by electron-deficient Rh 2 (CF 3 COO) 4 and the chiral rhodium(II) catalyst Rh 2 (S-TCPTTL) 4 which has greater steric repulsions from its ligands compared to Rh 2 (S-PTIL) 4 . 50…”
Section: N-acyliminopyridinium/quinolinium Ylidessupporting
confidence: 92%
“…[1][2][3][4] Modeling is exceptionally efficient in deciphering reaction mechanisms. [5][6][7][8][9][10][11][12][13][14] Isoxazole ring is a key structural moiety of valuable pharmaceutical substances (Figure 1). [15] Among them are antibiotics, [16][17][18][19] as cloxacillin, [16,18,20] dicloxacillin [16,18,[20][21][22] and flucloxacillin, [16,18,20,23,24] which were included in the WHO Model List of Essential Medicines and recommended for the treatment of a wide range of bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of quantum chemical modeling implemented in modern software packages have potentially high accuracy and require relatively small hardware resources and researcher‘s time [1–4] . Modeling is exceptionally efficient in deciphering reaction mechanisms [5–14] …”
Section: Introductionmentioning
confidence: 99%